Program Providers’ Perceptions of Restorative and Transformative Justice in the Context of Domestic Violence Offender Treatment in North Carolina - Campbell, Julia K. (Victims & offenders, 2024)
Restorative justice (RJ) and other innovative approaches are increasingly being considered in lieu of traditional legal responses to intimate partner violence (IPV) perpetration. This formative qualitative study investigated the perspectives of 29 North Carolina-based domestic violence intervention program (DVIP) providers, domestic violence service program providers, and North Carolina Coalition Against Domestic Violence staff members regarding RJ and transformative justice (TJ) in the context of DVIP programming. Participants had mixed opinions about integrating RJ and TJ practices into current offender treatment and cited structural and organizational barriers to adoption. Simultaneously, they emphasized the cruciality of expanding inter-organizational networks and uncoupling offender treatment from the legal system. Participants cited increased inter-organizational cooperation and community involvement as critical steps in modifying offender treatment to include more restorative principles. Policies and institutional practices that endorse RJ and TJ may improve the effectiveness and transformational capability of offender treatment and increase healing for survivors.